Reconstructing Qur’anic Theology beyond Madhhab: Maqāṣidī Reconciliative Approach of Al-Galayand - Asrizal Mustofa; Kharis Nugroho; Nurul Wahida Fauzi; Asd'a Amatullah (ZAD Al-Mufassirin, 2026)
Theological debates often developed into prolonged polemics that gradually diverted theological discourse from the primary objectives of Qur’anic guidance. This study aims to examine the conceptual foundations of al-Galayand’s project and to identify the interpretive approach underlying it through a maqāṣidī theoretical framework. Employing a qualitative library research method, the study analyzed al-Galayand’s major works, including ʿAqīdah Bilā Madhāhib, ʿAqīdah al-Tawḥīd, al-Tasāmuḥ ‘inda al-Ghazali, al-Ummah bi Ḥājah ilā Tajdīd Ta‘allum al-‘Aqīdah, Makānat al-‘Aql fī al-Qur’ān, ʿAqīdat al-Tawḥīd Dīn Jamīʿ al-Anbiyāʾ, and Taqrīb al-Turāth: Dar’ Taʿāruḍ al-ʿAql Wa al-Naql Li Shaykh al-Islām Ibn Taymiyyah. The analysis focuses on his critique of madhhab-centred theology and his method of engaging with Qur’anic theological discourse. The study argues al-Galayand’s theological reading can be characterized as a model of maqāṣidī reconciliative interpretation_an interpretative approach that integrates purposive Qur’anic theology with a reconciliatory perspective toward theological diversity. Through this approach, theological discourse is redirected toward the Qur’anic overaching objectives  of faith while simultaneously recognizing the legitimacy of theological plurality within the Islamic intellectual tradition.